Evaluation of biomarkers for in vitro prediction of drug‐induced nephrotoxicity: comparison of HK‐2, immortalized human proximal tubule epithelial, and primary cultures of human proximal tubular cells. Issue 3 (15th May 2015) - Huang, Johnny X.; Kaeslin, Geraldine; Ranall, Max V.; Blaskovich, Mark A.; Becker, Bernd; Butler, Mark S.; Little, Melissa H.; Lash, Lawrence H.; Cooper, Matthew A.
Abstract There has been intensive effort to identify in vivo biomarkers that can be used to monitor drug‐induced kidney damage and identify injury before significant impairment occurs. Kidney injury molecule‐1 (KIM‐1), neutrophil gelatinase‐associated lipocalin (NGAL), and human macrophage colony stimulating factor (M‐CSF) have been validated as urinary and plasma clinical biomarkers predictive of acute and chronic kidney injury and disease. Similar validation of a high throughput in vitro assay predictive of nephrotoxicity could potentially be implemented early in drug discovery lead optimization to reduce attrition at later stages of drug development. To assess these known in vivo biomarkers for their potential for in vitro screening of drug‐induced nephrotoxicity, we selected a panel of nephrotoxic agents and examined their effects on the overexpression of nephrotoxicity biomarkers in immortalized (HK‐2) and primary (commercially available and freshly in‐house produced) human renal proximal tubule epithelial cells. Traditional cytotoxicity was contrasted with expression levels of KIM‐1, NGAL, and M‐CSF assessed using ELISA and real‐time quantitative reverse transcription PCR. Traditional cytotoxicity assays and biomarker assays using HK‐2 cells were both unsuitable for prediction of nephrotoxicity. However, increases in protein levels of KIM‐1 and NGAL in primary cells were well correlated with dose levels of known nephrotoxic compounds, with limited correlation seen in M‐CSF protein and mRNA levels. These results suggest that profiling compounds against primary cells with monitoring of biomarker protein levels may have potential as in vitro predictive assays of drug‐induced nephrotoxicity.